Role of the Helicobacter pylori virulence factors vacuolating cytotoxin, CagA, and urease in a mouse model of disease. - Ghiara, P (1995)
The pathogenic role of Helicobacter pylori virulence factors has been studied with a mouse model of gastric disease. BALB/c mice were treated orally with different amounts of sonic extracts of cytotoxic H. pylori strains (NCTC 11637, 60190, 84-183, and 87A300 [CagA+/Tox+]). The pathological effects on histological sections of gastric mucosae were assessed and were compared with the effects of treatments with extracts from noncytotoxic strains (G21 and G50 [CagA-/Tox-]) and from strains that express either CagA alone (D931 [CagA+/Tox-]) or the cytotoxin alone (G104 [CagA-/Tox+]). The treatment with extracts from cytotoxic strains induced various epithelial lesions (vacuolation, erosions, and ulcerations), recruitment of inflammatory cells in the lamina propria, and a marked reduction of the mucin layer. Extracts of noncytotoxic strains induced mucin depletion but no other significant pathology. Crude extracts of strain D931, expressing CagA alone, caused only mild infiltration of inflammatory cells, whereas extracts of strain G104, expressing cytotoxin alone, induced extensive epithelial damage but little inflammatory reaction. Loss of the mucin layer was not associated with a cytotoxic phenotype, since this loss was observed in mice treated with crude extracts of all strains. The pathogenic roles of CagA, cytotoxin, and urease were further assessed by using extracts of mutant strains of H. pylori defective in the expression of each of these virulence factors. The results obtained suggest that (i) urease activity does not play a significant role in inducing the observed gastric damage, (ii) cytotoxin has an important role in the induction of gastric epithelial cell lesions but not in eliciting inflammation, and (iii) other components present in strains which carry the cagA gene, but distinct from CagA itself, are involved in eliciting the inflammatory response.